"That's Not Funny!" Identity and the organization of interaction on USA entertainment-political interviews. (June 2020) - Reijven, Menno H.; Grimshaw, Eean; Dori-Hacohen, Gonen
Abstract: Late-night talk shows have become a central venue for political communication in the U.S.A. In these interviews, entertainment and politics are both used and therefore we name them Entertainment-Political Interviews (EPIs). While research on such shows generally assumes that the EPI is a hybrid discourse, crafting entertainment and politics into one coherent discourse, this assumption has not been empirically justified. Using membership categorization analysis (MCA) to study how the participants self-categorize in the EPI, we illustrate how they orient to political and entertainment talk. First, by applying Sacks' (1972) hearer's maxim to its fullest extent, entertainment and politics are identified as independently foundational devices for the EPI. Second, only one of these devices is relevant at a time to shape a turn at talk. Third, still, each device is continuously relevant to the participants. Thus, the understanding of the activity is based on the separation of the device of politics and of entertainment. Therefore, we argue, the EPI does not result in a hybrid device with a hybrid form of talk, but rather, participants alternate between politics and entertainment.